An Exploration of Factors That Predict Advanced Placement Exam Success for Gifted Hispanic Students. Issue 4 (November 2019) - Graefe, Amy K.; Ritchotte, Jennifer A.
Hispanic students participate in advanced programming at a much lower rate than their White peers. Although Advanced Placement (AP) can have a positive impact on future academic success and attainment of long-term goals, limited research has investigated factors that contribute to AP success for gifted Hispanic students. This study examined factors potentially predictive of success on AP exams for gifted Hispanic students. Contrary to prior literature, findings revealed that race/ethnicity was not a factor that significantly affected AP success for these gifted students. In addition, when examining the performance of all the Hispanic AP students, the only factor that significantly contributed to passing an AP exam was identification as gifted. Implications for practice and suggestions for future research are discussed.